BeQuali, une archive en question - Sophie Duchesne; Mathieu Brugidou (Revue d'anthropologie des connaissances)
This paper addresses the difficulties generated by the archiving of data in social sciences and humanities through a case study: the set-up of a French qualitative archive, beQuali, whose first years (2006-2013) happened to be full of frictions. The article deals first with the consequences of the inflation of promises on the standardization of research practices. It then analyses the interpretative flexibility related to archiving and its difficult translation into a series of mediating objects. Lastly, the article shows the increasing disconnection between functioning and uses of the infrastructure and emphasizes some effects of the “excellence” policies on the team organization. The authors, who participated in beQuali’s set-up, conclude, with the required methodological step back, that political issues related to the making of this kind of equipment have to be taken into consideration and plead for questioning further existing qualitative archives.